Analisis Tindak Tutur Guru PGSD Dalam Pengembangan Keterampilan Berpikir Kritis Siswa Sekolah Dasar - Anggi Putri Relisa; Nur Azmi Alwi (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the role of teacher speech acts in developing elementary school students' critical thinking skills. Through qualitative descriptive methods, this research analyzes teacher speech acts based on four main types: locutionary, illocutionary, perlocutionary, and expressive. Data was collected through classroom observations and literature review. The results of the analysis show that the combination of these speech acts has a significant impact in stimulating students' analytical thinking, broadening their understanding, and providing emotional support. This research provides important insights for the development of more effective teaching methods in elementary schools and emphasizes the importance of developing critical thinking skills from an early age. In conclusion, this research contributes to our understanding of how teachers' speech acts can shape students' thinking patterns and design more innovative teaching strategies.